Supported VOCs treatment catalyst as well as preparation method and application thereof
By dry mixing FCC waste catalyst powder with γ-Al2O3 and adding binder and pore reamer, dry molding and complete equal volume impregnation method loading iron nitrate and manganese nitrate, the problem of forming FCC waste catalyst powder and wastewater problems are solved. , realizes efficient VOCs waste gas treatment and resource utilization, and has good economic and environmental benefits.
Patent Information
- Application Number
- CN202411397080.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-20
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-07
AI Technical Summary
The poor compressibility and low mechanical strength of FCC waste catalyst powder lead to the inability to directly mold into a fixed bed catalyst. The existing preparation methods produce a large amount of wastewater, and the green process has not been realized.
Use waste catalyst powder to dry mix with γ-Al2O3, add binder and pore reamer to obtain a molded catalyst support by dry molding, and loading iron nitrate and manganese nitrate by complete equal volume impregnation method to prepare a supported VOCs treatment catalyst , achieve water-free forming and wastewater reduction.
Improve the compressibility of waste catalyst powder and the mechanical strength of the molded body, and realize efficient management of VOCs waste gas. The catalyst can reach an ethylbenzene conversion rate of more than 99.5% at 300-500℃, and the process is completely free of wastewater, which is economical. and environmental benefits.
Smart Images

Figure BDA0005074088140000061 
Figure BDA0005074088140000071 
Figure BDA0005074088140000072
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of harmless disposal of hazardous solid waste resources, and relates to a supported VOCs treatment catalyst and a preparation method and application thereof. Background Art
[0002] Fluidized catalytic cracking (FCC) is currently the main method for oil refining, and FCC catalyst has become the most widely used catalyst in the current oil refining field. It is estimated that by 2025, the global oil catalytic cracking capacity will reach 1 billion tons / year, and during the production process, FCC catalysts will produce cyclone fine powder waste catalysts, accounting for 20% of the total amount of FCC waste catalysts. FCC waste catalysts contain a variety of transition metal elements, which are both hazardous wastes and major secondary metal resources. If they are not properly disposed of, they will cause environmental pollution and waste of resources. Therefore, preparing cyclone fine powder FCC waste catalysts into fixed bed catalysts is a way to achieve resource utilization.
[0003] Chinese invention patent application CN116943636A discloses a method for preparing a waste FCC loaded manganese oxide columnar low-temperature SCR denitration catalyst, by adding a harmful metal immobilization aid (500°C calcined hydrotalcite) and loading manganese oxide active components to prepare a catalyst powder with low-temperature SCR denitration activity; and then optimizing its bonding formula system to obtain a low-temperature SCR denitration catalyst. This method generates a large amount of metal ion-containing wastewater during the preparation of the carrier raw material, and the production process is not completely a green process.
[0004] The key to preparing a fixed bed catalyst from cyclone fine powder FCC waste catalyst is molding. However, due to the certain wear resistance and high particle strength of FCC waste catalyst, the compressibility of FCC waste catalyst powder is very poor and it cannot be directly pressed into tablets. Summary of the invention
[0005] The purpose of the present invention is to improve the compressibility of waste catalyst powder and the mechanical strength of powder molding in order to solve the above problems, and to provide a method for forming waste catalyst powder and preparing a catalyst for exhaust gas treatment by using waste catalyst powder such as FCC waste catalyst powder and γ-Al2O3 as raw materials, adding a binder and a pore expander.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A supported VOCs treatment catalyst is prepared by dry-mixing waste catalyst powder and γ-Al2O3 as raw materials to obtain a mixed material, which is then mixed with a binder and a pore-enlarging agent to obtain a base material powder, and then dry-molding is used to obtain a molded catalyst carrier, and a mixed impregnation solution of ferric nitrate and manganese nitrate is prepared to obtain the supported VOCs treatment catalyst by a complete equal volume impregnation method.
[0008] Another object of the present invention is to provide a method for preparing a supported VOCs treatment catalyst, comprising the following steps:
[0009] Step S1, putting the waste catalyst powder and γ-Al2O3 into a kneader for dry mixing to obtain a mixed material, and then putting a binder and a pore-enlarging agent into the kneader for further dry mixing to obtain a base material powder;
[0010] Step S2, dry molding: the base material powder obtained in step S1 is extruded and molded in a rotary tablet press, and calcined to obtain a molded catalyst carrier;
[0011] Step S3, preparing a mixed impregnation solution with a concentration of 0.15 to 0.94 g / mL of iron nitrate and a concentration of 0.10 to 0.34 g / mL of manganese nitrate, using a complete equal volume impregnation method, impregnating the formed catalyst support in the mixed impregnation solution at room temperature for 12 to 24 hours, filtering, collecting the residual impregnation solution, and drying and calcining the obtained solid particles to obtain a one-impregnation-one-calcination catalyst;
[0012] Step S4, soaking the impregnated and baked catalyst in the residual solution at room temperature, and waiting for the residual solution to be completely absorbed by the impregnated and baked catalyst, and then drying and baking in sequence to obtain a supported VOCs treatment catalyst.
[0013] In step S1, the waste catalyst powder is the waste catalyst powder from all fluidized bed reaction processes, or the waste catalyst particles from fixed bed reaction processes, obtained by crushing. Preferably, the waste catalyst powder is the waste catalyst powder produced from the FCC catalyst production process.
[0014] The particle size of the waste catalyst powder is less than 60 microns.
[0015] The particle size of the γ-Al2O3 is ≤20 nanometers.
[0016] The mass ratio of the waste catalyst powder to γ-Al2O3 is 9:1 to 1:9.
[0017] The mass ratio of the mixed material to the adhesive is 300:1 to 300:4.
[0018] The adhesive is one of sodium carboxymethyl cellulose, stearic acid, polyvinyl alcohol and sesbania gum powder.
[0019] The mass ratio of the mixed material to the pore-enlarging agent is 300:1 to 300:7.
[0020] The pore-enlarging agent is one of polyethylene glycol 20000, Printex U-type carbon black, hydroxypropyl methylcellulose and soluble starch.
[0021] The angle of repose of the base material powder is 40.1-44.0°.
[0022] Preferably, the base material powder is prepared by putting the waste catalyst powder and γ-Al2O3 into a kneader, dry mixing for 30 to 60 minutes to obtain a mixture, and then putting a binder and a pore expanding agent into the kneader and continuing to dry mix for 30 to 60 minutes to obtain a base material powder.
[0023] The molding method of the molded catalyst carrier described in the present invention is dry molding, and no water is needed during the molding process.
[0024] In step S2, the extrusion pressure of the rotary tablet press is 3-8 kN, and the rotation speed is 10-25 r / min.
[0025] The calcination temperature is 450-600° C., and the calcination time is 2-4 hours.
[0026] In step S3, the dosage ratio of the catalyst forming carrier and the mixed impregnation liquid is 10:10.8 g / mL.
[0027] The drying temperature is 110-130°C, and the drying time is 10-20 hours; the calcining temperature is 450-600°C, and the calcining time is 2-4 hours.
[0028] In step S4, generally, the impregnated and baked catalyst is immersed in the impregnation solution at room temperature for 6 to 12 hours, and the impregnation solution is completely absorbed by the impregnated and baked catalyst.
[0029] The drying temperature is 110-130°C, and the drying time is 10-20 hours; the calcining temperature is 450-600°C, and the calcining time is 2-4 hours.
[0030] Another object of the present invention is to provide application of the catalyst in catalytic oxidation purification of waste gas containing VOCs.
[0031] A method for catalytic oxidation purification of VOCs-containing waste gas, comprising: using the catalyst to catalytically oxidize the VOCs-containing waste gas, the reaction conditions are: the ethylbenzene content in the VOCs-containing waste gas is 500-1500ppm, the reaction space velocity is 1500-12000ml·g -1 ·h -1, the reaction temperature is 300-500℃.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1) The present invention aims at the problem of disposing waste catalyst powder. By adding a series of molding aids and optimizing the molding process, the sheet carrier is formed. Then, the cheap and easily available iron element is loaded on the molding carrier by the double leaching and double baking method, and the manganese element is used as the second metal to further prepare an environmentally friendly bimetallic oxide catalyst that can be used for VOCs waste gas treatment, thus realizing the resource utilization of waste. Moreover, the catalyst has a good catalytic oxidation effect on VOCs, and can achieve an ethylbenzene conversion rate of more than 99.5% at 300-500°C, and the ethylbenzene outlet concentration can be reduced to 25mg / m 3 The following achieves waste gas treatment, which has both economic and environmental benefits.
[0034] 2) The present invention adopts dry tableting, and no water is needed in the process; at the same time, completely equal volume impregnation is adopted, so that no waste water is generated in the process, which is a green waste recycling method. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below through specific implementation methods.
[0036] The FCC spent catalyst powder comes from Shandong Duoyou Technology Co., Ltd., with a particle size of less than 60 microns (i.e., passing through a 230-mesh sieve); γ-Al2O3, with a particle size of ≤20 nm.
[0037] Comparative Example 1
[0038] The rotary tablet press punch extrusion force was set to 4 kN, and the rotation speed was set to 15 r / min. 300 parts by mass of FCC waste catalyst powder were attempted to be extruded in the rotary tablet press, but demolding was difficult and could not be performed.
[0039] Comparative Example 2
[0040] The rotary tablet press punch extrusion pressure was set to 4 kN, the rotation speed was set to 15 r / min, and 300 parts by mass of γ-Al2O3 were attempted to be extruded in the rotary tablet press, but the discharged material was broken and could not be formed.
[0041] Comparative Example 3
[0042] FCC waste catalyst powder and γ-Al2O3 are put into a kneader at a mass ratio of 6:4, and dry mixed for 60 minutes to obtain a base material powder; the extrusion force of the rotary tablet press punch is set to 8 kN, and the rotation speed is set to 15 r / min, 300 parts by mass of the base material powder are extruded in the rotary tablet press to obtain a sheet-like molded carrier; the molded carrier is placed in a muffle furnace, the temperature is adjusted to 550°C, and calcined for 2 hours to obtain a molded catalyst carrier C3.
[0043] Example 1
[0044] A method for tabletting waste catalyst powder, comprising the following steps:
[0045] S1, FCC waste catalyst powder and γ-Al2O3 are put into a kneader at a mass ratio of 6:4, and dry-mixed for 60 minutes to obtain 300 parts by mass of a mixed material, and then 2 parts by mass of sesbania gum powder and 2.5 parts by mass of hydroxypropyl methylcellulose are put into the kneader, and dry-mixed for another 60 minutes to obtain a base material powder;
[0046] S2. Set the punch extrusion pressure of the rotary tablet press to 8 kN and the rotation speed to 15 r / min. Extrude the base material powder obtained in step S1 in the rotary tablet press to obtain a sheet-shaped formed carrier; put the formed carrier into a muffle furnace, adjust the temperature to 550° C., and calcine for 2 hours to obtain a formed catalyst carrier C4.
[0047] Example 2
[0048] A method for tabletting waste catalyst powder, comprising the following steps:
[0049] S1. Put FCC waste catalyst powder and γ-Al2O3 into a kneader at a mass ratio of 8:2, dry mix for 30 minutes to obtain 300 parts by mass of a mixture, then put 1 part by mass of stearic acid and 1 part by mass of Printed U-type carbon black into the kneader, and continue dry mixing for 30 minutes to obtain a base material powder;
[0050] S2. Set the rotary tablet press punch extrusion pressure to 10 kN and the rotation speed to 25 r / min. Extrude the base material powder obtained in step S1 in the rotary tablet press to obtain a sheet-shaped carrier; put the molded carrier into a muffle furnace, adjust the temperature to 450° C., and calcine for 3 hours to obtain a molded catalyst carrier C5.
[0051] Example 3
[0052] A method for tabletting waste catalyst powder comprises the following steps:
[0053] S1. Put FCC waste catalyst powder and γ-Al2O3 into a kneader at a mass ratio of 7:3, dry-mix for 40 minutes to obtain 300 parts by mass of a mixture, then put 3 parts by mass of stearic acid and 7 parts by mass of hydroxypropyl methylcellulose into the kneader, and continue dry-mixing for 40 minutes to obtain a base material powder;
[0054] S2. Set the rotary tablet press punch extrusion pressure to 6 kN and the rotation speed to 20 r / min. Extrude the base material powder obtained in step S1 in the rotary tablet press to obtain a sheet-shaped carrier; put the molded carrier into a muffle furnace, adjust the temperature to 550°C, and calcine for 4 hours to obtain a molded catalyst carrier C6.
[0055] Example 4
[0056] A method for tabletting waste catalyst powder comprises the following steps:
[0057] S1, the waste fluidized bed catalyst powder and γ-Al2O3 were put into a kneader at a mass ratio of 5:5, and dry mixed for 50 minutes to obtain 300 parts by mass of a mixed material, and then 2 parts by mass of sesbania gum powder and 5.5 parts by mass of hydroxypropyl methylcellulose were put into the kneader, and the dry mixing was continued for 50 minutes to obtain a base material powder;
[0058] S2. Set the extrusion pressure of the rotary tablet press punch to 8 kN and the rotation speed to 10 r / min. Extrude the base material powder obtained in step S1 in the rotary tablet press to obtain a sheet-shaped carrier; put the molded carrier into a muffle furnace, adjust the temperature to 600°C, and calcine for 4 hours to obtain a molded catalyst carrier C7.
[0059] Example 5
[0060] A method for tabletting waste catalyst powder comprises the following steps:
[0061] S1, FCC waste catalyst powder and γ-Al2O3 were put into a kneader at a mass ratio of 6:4, and dry-mixed for 60 minutes to obtain 300 parts by mass of a mixed material, and then 2 parts by mass of sesbania gum powder and 4 parts by mass of hydroxypropyl methylcellulose were put into the kneader, and dry-mixed for 60 minutes to obtain a base material powder;
[0062] S2. Set the rotary tablet press punch extrusion pressure to 8 kN and the rotation speed to 10 r / min. Extrude the base material powder obtained in step S1 in the rotary tablet press to obtain a sheet-shaped carrier; put the molded carrier into a muffle furnace, adjust the temperature to 550°C, and calcine for 2 hours to obtain a molded catalyst carrier C8.
[0063] Example 6
[0064] A method for preparing a catalyst for exhaust gas treatment comprises the following steps:
[0065] S1. Prepare a mixed impregnation solution with a concentration of 0.15 g / mL of iron nitrate and a concentration of 0.34 g / mL of manganese nitrate, take 10 g of the catalyst-shaped C8 carrier and add it to 10.8 mL of the mixed impregnation solution, impregnate for 12 hours, filter, collect the remaining impregnation solution, and first put the obtained solid particles into an oven at 130° C. and dry for 12 hours, and then put them into a muffle furnace at 450° C. and roast them for 4 hours to obtain a one-impregnation and one-roasting catalyst;
[0066] S2. The one-impregnation-one-baking catalyst prepared in step S1 is further impregnated in the residual solution collected in step S1 for 12 hours to allow all the residual solution to be completely absorbed. The catalyst is first placed in an oven at 130° C. for 12 hours and then placed in a muffle furnace for calcination at 450° C. for 4 hours to obtain a two-impregnation-two-baking catalyst SC1.
[0067] Example 7
[0068] A method for preparing a catalyst for exhaust gas treatment comprises the following steps:
[0069] S1. Prepare a mixed impregnation solution with a concentration of 0.95 g / mL of iron nitrate and a concentration of 0.10 g / mL of manganese nitrate, add 10 g of the catalyst-shaped C8 carrier to 10.8 mL of the mixed impregnation solution, impregnate for 16 hours, filter, collect the residual impregnation solution, and first put the obtained solid particles into an oven at 120° C. and dry for 15 hours, and then put them into a muffle furnace at 550° C. and roast them for 3 hours to obtain a one-impregnation and one-roasting catalyst;
[0070] S2. The one-impregnation-one-baking catalyst prepared in step S1 is further impregnated in the residual solution collected in step S1 for 12 hours to allow all the residual solution to be completely absorbed. The catalyst is first placed in an oven at 120° C. for drying for 15 hours, and then placed in a muffle furnace for calcination at 550° C. for 3 hours to obtain a two-impregnation-two-baking catalyst SC2.
[0071] Example 8
[0072] A method for preparing a catalyst for exhaust gas treatment comprises the following steps:
[0073] S1. Prepare a mixed impregnation solution with a concentration of 0.49 g / mL of iron nitrate and a concentration of 0.21 g / mL of manganese nitrate, add 10 g of the catalyst-shaped C8 carrier to 10.8 mL of the mixed impregnation solution, impregnate for 20 hours, filter, collect the residual impregnation solution, and first place the obtained solid particles in an oven at 110° C. to dry for 18 hours, and then place them in a muffle furnace at 650° C. to roast for 2 hours to obtain a one-impregnation and one-roasting catalyst;
[0074] S2. The one-impregnation-one-baking catalyst prepared in step S1 is further impregnated in the residual solution collected in step S1 for 12 hours to allow all the residual solution to be completely absorbed. The catalyst is first placed in an oven at 110° C. for drying for 12 hours, and then placed in a muffle furnace for calcination at 650° C. for 2 hours to obtain a two-impregnation-two-baking catalyst SC3.
[0075] Example 9
[0076] A method for preparing a catalyst for exhaust gas treatment comprises the following steps:
[0077] S1. Prepare a mixed impregnation solution with a concentration of 0.70 g / mL of iron nitrate and a concentration of 0.15 g / mL of manganese nitrate, add 10 g of the catalyst-shaped C8 carrier to 10.8 mL of the mixed impregnation solution, impregnate for 24 hours, filter, collect the residual impregnation solution, and first place the obtained solid particles in an oven at 110° C. to dry for 20 hours, and then place them in a muffle furnace at 550° C. to roast for 2 hours to obtain a one-impregnation-one-roasting catalyst;
[0078] S2. The one-impregnation-one-baking catalyst prepared in step S1 is further impregnated in the residual solution collected in step S1 for 12 hours to allow all the residual solution to be completely absorbed. The catalyst is first placed in an oven at 110° C. for drying for 20 hours, and then placed in a muffle furnace for calcination at 550° C. for 2 hours to obtain a two-impregnation-two-baking catalyst SC4.
[0079] Example 10
[0080] A method for preparing a catalyst for exhaust gas treatment comprises the following steps:
[0081] S1. Prepare a mixed impregnation solution with a concentration of 0.95 g / mL of iron nitrate and 0.27 g / mL of manganese nitrate, add 10 g of the catalyst-shaped C8 carrier to 10.8 mL of the mixed impregnation solution, impregnate for 16 hours, filter, collect the residual impregnation solution, and first put the obtained solid particles into an oven at 110° C. and dry for 12 hours, and then put them into a muffle furnace at 550° C. and roast them for 2 hours to obtain a one-impregnation and one-roasting catalyst;
[0082] S2. The one-impregnation-one-baking catalyst prepared in step S1 is further impregnated in the residual solution collected in step S1 for 16 hours to allow all the residual solution to be completely absorbed. The catalyst is first placed in an oven at 110° C. for 10 hours and then placed in a muffle furnace for calcination at 550° C. for 2 hours to obtain a two-impregnation-two-baking catalyst SC5.
[0083] Table 1. Angle of repose of base powder, mechanical strength, specific surface area and average pore size of carrier particles of Examples 1-5 and Comparative Examples
[0084]
[0085]
[0086] Table 2. Mechanical strength, specific surface area and average pore size of catalysts in Examples 6 to 10
[0087]
[0088] The angle of repose of FCC waste catalyst powder is 28.5°. Since FCC waste catalyst has certain wear resistance, the catalyst particles are hard, and the powder has good fluidity, but its compressibility is low, so it is difficult to demold during the tableting process, resulting in failure to form. The angle of repose of γ-Al2O3 is 48.1°. During the tableting process, the base material powder has extremely poor fluidity, and the powder cannot fill the mold, resulting in broken material. In comparison, the base material powder prepared in Examples 1 to 5 has an angle of repose in the range of 40.1-44.0°, has excellent fluidity, and the powder can be successfully tableted.
[0089] Compared with Comparative Example 3, Example 1 added a binder and a pore expander, and the radial compressive strength was increased by 14.9% and the average pore size was increased by 9.7%, indicating that the addition of a binder can enhance the strength of the carrier to a certain extent, while the pore expander is helpful to the pore size of the carrier.
[0090] The mechanical strength, specific surface area and average pore size of the carrier samples prepared in Example 1 to Example 5 are shown in Table 1. The mechanical strength, specific surface area and average pore size of the catalyst samples prepared in Example 6 to Example 10 are shown in Table 1 and Table 2. It can be seen from Tables 1 and 2 that:
[0091] Compared with Comparative Example 1, the carrier samples prepared in Examples 1 to 5 all achieved sheet molding, indicating that adding molding aids can effectively change the physical and chemical properties of the carrier. The radial compressive strength of Example 4 decreased by 34.3% compared with Example 3, indicating that moderately increasing the proportion of the pore expander can make the carrier surface have a rich pore structure, but it causes the strength to deteriorate, indicating that there is an optimal value for the amount of pore expander, and excessive addition will lead to strength deterioration. Compared with Comparative Example 3, the radial compressive strength of the carrier C8 prepared by adding sesbania gum powder and hydroxypropyl methylcellulose in Example 5 reached 108.8N·cm -1 , with a specific surface area of 176.5m 2 ·g -1 , the average pore size can reach 10.7nm, and the carrier exhibits high mechanical strength and relatively good specific surface area, which can not only ensure that the carrier has sufficient stability in practical applications, but also provide it with a good pore structure, which helps to improve the catalytic performance. In Examples 6 to 10, the carrier C8 prepared in Example 5 was subjected to an impregnation loading treatment to prepare a catalyst sample. The mechanical strength of the catalyst did not change significantly, but the specific surface area and average pore size became smaller, indicating that the active components entered the carrier pores and the carrier could effectively load the active components.
[0092] The catalytic performance of the catalyst particles obtained in Example 6-Example 10 was tested. The catalyst catalytic oxidation experiment was carried out in a fixed bed reactor at normal pressure (with an inner diameter of φ=30 mm). The reaction column filler was a porcelain ring, and the catalyst was loaded in the middle section of the reactor. The ethylbenzene gas generator was placed in an ice-water bath to ensure that the ethylbenzene vapor pressure was 0°C. The gas flow rate was adjusted by a gas mass flow controller and a rotor flowmeter to provide ethylbenzene reaction gas with a stable flow rate. The ethylbenzene concentration of the outlet tail gas after the catalytic reaction was measured using the FID detector of the GC9790Plus chromatograph produced by Zhejiang Fuli Analytical Instrument Co., Ltd.
[0093] Calculation formula for export ethylbenzene conversion rate:
[0094]
[0095] In the formula, x Toluene is the conversion rate of ethylbenzene, c in 、c out Ethylbenzene inlet and outlet concentrations, respectively.
[0096] Example 6 Catalyst Performance Test Experimental reaction conditions are: ethylbenzene inlet concentration is 750ppm, space velocity is 3000mL·g -1 ·h -1 , the reaction temperature is 400℃.
[0097] Example 7 Catalyst Performance Test Experimental reaction conditions are: ethylbenzene inlet concentration is 500 ppm, space velocity is 12000 mL·g -1 ·h -1 , the reaction temperature is 440℃.
[0098] Example 8 Catalyst Performance Test Experimental reaction conditions are: ethylbenzene inlet concentration is 1000 ppm, space velocity is 6000 mL·g -1 ·h -1 , the reaction temperature is 420℃.
[0099] Example 9 Catalyst Performance Test Experimental reaction conditions are: ethylbenzene inlet concentration is 1500ppm, space velocity is 9000mL·g -1 ·h -1 , the reaction temperature is 500℃.
[0100] Example 10 Catalyst Performance Test Experimental reaction conditions are: ethylbenzene inlet concentration is 1250ppm, space velocity is 1500mL·g -1 ·h -1 , the reaction temperature is 340℃.
[0101] Table 3. Ethylbenzene conversion rate and outlet concentration
[0102] Catalyst No. Conversion rate / % <![CDATA[Outlet concentration / mg / m 3 > Catalyst SC1 99.61 18.6 Catalyst SC2 99.57 20.4 Catalyst SC3 99.55 21.4 Catalyst SC4 99.47 25.1 Catalyst SC5 99.71 13.6
[0103] The experimental conversion rate of ethylbenzene and the outlet concentration of ethylbenzene of the catalyst samples prepared in Examples 6 to 10 are shown in Table 3. It can be seen from Table 3 that:
[0104] The flake catalyst samples prepared in Examples 6 to 10 can effectively catalyze the oxidation of ethylbenzene and exhibit excellent catalytic oxidation performance at 300-500°C. The catalyst SC2 in Example 7 has a high oxidation performance at a space velocity of 12000 mL·g -1 ·h -1 , the conversion rate can reach 99.51% at a temperature of 440℃, and the outlet concentration can be reduced to 20.4mg / m 3 , indicating that the prepared catalyst can adapt to high space velocity conditions; Example 10 catalyst SC5 at a space velocity of 1500mL·g -1 ·h -1 , the conversion rate can reach 99.71% at a temperature of 340°C, indicating that reducing the space velocity can increase the contact time between the reactants and the catalyst and reduce the catalytic reaction temperature; Example 8 catalyst SC3 at a space velocity of 6000 mL·g -1 ·h -1 The conversion rate can reach 99.55% and the outlet concentration can be reduced to 21.4mg / m 3 , meeting the requirements of industrial applications.
Claims
1. A supported VOCs treatment catalyst, characterized in that: The method uses waste catalyst powder and γ-Al2O3 as raw materials, dry-mixes the mixed material, mixes the mixed material with a binder and a pore-enlarging agent to obtain a base material powder, and then adopts a dry molding method to obtain a catalyst molding carrier, prepares a mixed impregnation solution of ferric nitrate and manganese nitrate, and adopts a completely equal volume impregnation method to prepare a supported VOCs treatment catalyst.
2. The supported VOCs treatment catalyst according to claim 1, characterized in that: The mass ratio of the waste catalyst powder to γ-Al2O3 is 9:1 to 1:9; the mass ratio of the mixture to the adhesive is 300:1 to 300:4; the mass ratio of the mixture to the pore-enlarging agent is 300:1 to 300:
7.
3. The supported VOCs treatment catalyst according to claim 1, characterized in that: The adhesive is one of sodium carboxymethyl cellulose, stearic acid, polyvinyl alcohol, and sesbania gum powder; the pore expanding agent is one of polyethylene glycol 20000, Printex U type carbon black, hydroxypropyl methylcellulose, and soluble starch.
4. The supported VOCs treatment catalyst according to claim 1, characterized in that: The angle of repose of the base material powder is 40.1-44.0°.
5. A method for preparing a supported VOCs treatment catalyst, characterized in that: The steps include: Step S1, putting the waste catalyst powder and γ-Al2O3 into a kneader for dry mixing to obtain a mixed material, and then putting a binder and a pore-enlarging agent into the kneader for further dry mixing to obtain a base material powder; Step S2, dry molding: the base material powder obtained in step S1 is extruded and molded in a rotary tablet press, and calcined to obtain a molded catalyst carrier; Step S3, preparing a mixed impregnation solution with a concentration of 0.15 to 0.94 g / mL of iron nitrate and a concentration of 0.10 to 0.34 g / mL of manganese nitrate, using a complete equal volume impregnation method, impregnating the catalyst shaped carrier in the mixed impregnation solution at room temperature for 12 to 24 hours, filtering, collecting the residual impregnation solution, and drying and calcining the obtained solid particles to obtain a one-impregnation-one-calcination catalyst; Step S4, soaking the impregnated and baked catalyst in the residual solution at room temperature, and waiting for the residual solution to be completely absorbed by the impregnated and baked catalyst, and then drying and baking in sequence to obtain a supported VOCs treatment catalyst.
6. The method for preparing a supported VOCs treatment catalyst according to claim 5, characterized in that: In step S1, waste catalyst powder and γ-Al2O3 are put into a kneader and dry-mixed for 30 to 60 minutes to obtain a mixed material, and then a binder and a pore-enlarging agent are put into the kneader and dry-mixed for another 30 to 60 minutes to obtain a base material powder.
7. The method for preparing a supported VOCs treatment catalyst according to claim 5, characterized in that: In step S2, the extrusion pressure of the rotary tablet press is 3-8 kN, and the rotation speed is 10-25 r / min; the calcination temperature is 450-600° C., and the calcination time is 2-4 h.
8. The method for preparing a supported VOCs treatment catalyst according to claim 5, characterized in that: In step S3, the drying temperature is 110-130°C, and the drying time is 10-20 hours; the calcination temperature is 450-600°C, and the calcination time is 2-4 hours; in step S4, the drying temperature is 110-130°C, and the drying time is 10-20 hours; the calcination temperature is 450-600°C, and the calcination time is 2-4 hours.
9. Use of the catalyst according to claim 1 in catalytic oxidation purification of waste gas containing VOCs.
10. A method for catalytic oxidation purification of waste gas containing VOCs, characterized in that: include: The catalyst of claim 1 is used to catalyze and oxidize the VOCs-containing waste gas, and the reaction conditions are: the ethylbenzene content in the VOCs-containing waste gas is 500-1500ppm, and the space velocity is 1500-12000ml·g -1 ·h -1 , the reaction temperature is 300-500°C.
Citation Information
Patent Citations
Forming preparation method of waste FCC (fluid catalytic cracking) loaded manganese oxide columnar low-temperature SCR (selective catalytic reduction) denitration catalyst
CN116943636A